BENTUK DAN STRUKTUR PENYAJIAN MUSIK KULINTANG PADA PROSES ARAK-ARAKAN DALAM ADAT PERNIKAHAN SUKU KOMERING DI OKU TIMUR - Dedy Firmansyah (Besaung : Jurnal Seni Desain dan Budaya, 2016)
This research tittle is the Form And Strucuture Of Presentation Of Music In Process Kulintang Procession Komering Interest In Traditional Wedding In Oku East. Kulintang music is means of a tribal society of komering in marriage. That staging in customery marriage are parade process, milur dance, giving the customery law, and sada sabai dance. But in its development nowadays the existence of kulintang music is declining in customery marriage.Based on the fact, this research aims to reveal the factors that affect the existence of kulintang music in East OKU. Besides, this research to do the description of analysis form and structure of kulintang music in every stage of the komering family marriage. Analysis includes the elements of musical the form and structure of the prersensation of kulintang music. The technique of collecting data to do with an observation, interviews, study says and documents. For analysis then used the method of analysis form and structure of music. In addition to the existence and the dynamics of the music kulintang not justbe descriptive, then this research will borrow the concepts of culture, music, and social community to have a perspective that is analytical. The study conclude that the cause of the decrease existence of the kulintang music in east OKU is because the disappearance of clan system in 1979. Clans system that change into district made there was no more loyality to the customery marriage process that use kulintang music. Internal and external factor are also influence thing to the existence of kulintang music. That internal and external factor consist of management, less of capability to play kulintang, motivation, finance, government role, and influence goreign culture. Keywords: kulintang; customery marriage; dynamics; form and structure music